1996
DOI: 10.1161/01.cir.94.6.1471
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones Prolong the QT Interval and Downregulate Potassium Channel Expression in the Rabbit Heart

Abstract: The association between hormone-induced changes in baseline QT interval and the mRNA level for these channels suggests that sex hormones may play a critical role in regulating cardiac repolarization. However, the changes in baseline QT and potassium channel mRNA after hormone treatment were not concordant with the changes in QT interval after the infusion of quinidine, after which E2-treated animals responded similarly to controls (18.4 +/- 4.6% and 19.3 +/- 4.6% increase in QT interval, respectively) and DHT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
255
4
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(276 citation statements)
references
References 23 publications
15
255
4
2
Order By: Relevance
“…Sex and hormonal differences in ion channel distribution have been described in the heart and could cause alterations in disease penetrance. 23 It is also not known if other clinical conditions that cause STE or J-point elevation (ischemia, hypothermia, acidosis) cause arrhythmias by mechanisms similar to the Brugada syndrome. The identification of novel genes that cause the Brugada syndrome and the correlation of phenotype to genotype may lead to improvements in diagnosis, assessment of prognosis, and choice of therapeutic alternatives for patients with this rare inherited propensity to arrhythmias.…”
Section: Molecular Basis Of the Brugada Syndromementioning
confidence: 99%
“…Sex and hormonal differences in ion channel distribution have been described in the heart and could cause alterations in disease penetrance. 23 It is also not known if other clinical conditions that cause STE or J-point elevation (ischemia, hypothermia, acidosis) cause arrhythmias by mechanisms similar to the Brugada syndrome. The identification of novel genes that cause the Brugada syndrome and the correlation of phenotype to genotype may lead to improvements in diagnosis, assessment of prognosis, and choice of therapeutic alternatives for patients with this rare inherited propensity to arrhythmias.…”
Section: Molecular Basis Of the Brugada Syndromementioning
confidence: 99%
“…However, Drici et al 21 demonstrated that testosterone and estrogen treatment in castrated female rabbits downregulates message levels of certain potassium channels. mRNA levels of HK2 (also known as hKv1.5, a human clone of the ultrarapidly activating delayed rectifier, I Kur ) 22 were reduced compared with placebo-treated rabbits.…”
Section: Mechanism Of Dht Actionmentioning
confidence: 99%
“…However, their mRNA data did not correspond with the changes in QT intervals that they noted. 21 Liu et al 8 evaluated sex-related differences in 3 major repolarizing K ϩ currents (I to , I K1 , and I Kr ) in the heart. They found no difference in I to density between male and female rabbits and reported a significant difference in I K1 at a single voltage, Ϫ50 mV (1.46Ϯ0.06 pA/pF in females and 1.67Ϯ0.08 pA/pF in males), but no difference at any other voltages.…”
Section: Mechanism Of Dht Actionmentioning
confidence: 99%
“…It is suggested that stressful situations during ovulatory periods and menstruation may cause increased 17-hydroxy corticosterone levels with resulting eosinopenia 2 . Platelet function is periodically altered during the ovarian cycle due to the influence of progesterone and estrogen on Von Willebrand factor concentrations 3 . Ovarian hormones influence almost all the systems of the body.…”
Section: Introductionmentioning
confidence: 99%